Impact of a rigid body against a half-infinite elastic bar - To, Nguyen Dang (Vietnam Journal of Mechanics, 1988)
The solution of the impact - problems of a rigid body against an elastic bar arc before based on the classical longitudinal vibration theory of elastic bar. In this paper, we are using a more precise theory to deal with the impact problem of a rigid body against a half -infinite elastic bar with an elastic gasket. This problem is solved completely.